2005
DOI: 10.1371/journal.pgen.0020168.eor
|View full text |Cite
|
Sign up to set email alerts
|

Forces Shaping the Fastest Evolving Regions in the Human Genome

Abstract: Comparative genomics allow us to search the human genome for segments that were extensively changed in the last ;5 million years since divergence from our common ancestor with chimpanzee, but are highly conserved in other species and thus are likely to be functional. We found 202 genomic elements that are highly conserved in vertebrates but show evidence of significantly accelerated substitution rates in human. These are mostly in non-coding DNA, often near genes associated with transcription and DNA binding. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
137
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(147 citation statements)
references
References 43 publications
7
137
1
2
Order By: Relevance
“…The evolution of these regulatory systems is one of the most important problems in evolutionary biology at present, but unfortunately this issue has not been studied in a comprehensive manner. A number of authors (e.g., 4,11,14,57,134,136) have studied the evolution of cis-regulatory and other elements by using statistical methods and concluded that their evolution was aided by positive selection. However, this conclusion appears to contradict the fact that these elements are generally highly conserved.…”
Section: Discussionmentioning
confidence: 99%
“…The evolution of these regulatory systems is one of the most important problems in evolutionary biology at present, but unfortunately this issue has not been studied in a comprehensive manner. A number of authors (e.g., 4,11,14,57,134,136) have studied the evolution of cis-regulatory and other elements by using statistical methods and concluded that their evolution was aided by positive selection. However, this conclusion appears to contradict the fact that these elements are generally highly conserved.…”
Section: Discussionmentioning
confidence: 99%
“…So-called human-accelerated regions (HAREs) have been increasingly implicated in cortical evolution [52,58].…”
Section: Hare5mentioning
confidence: 99%
“…Intriguingly, an independent study on expression of intergenic sequences in human and chimpanzee shows conservation of expression of noncoding RNAs in equivalent genomic positions, but not conservation of the RNA sequences, demonstrating that that noncoding RNAs are under expression constraints, particularly in brain [24]. Instead of looking for similarity of expression, Pollard and colleagues [25] looked for differences between human and chimpanzee. They analyzed genomic regions that evolve faster than neutral regions (evidence of positive selection) and identified about 200 of these regions.…”
Section: Introductionmentioning
confidence: 99%